Stand structure and species composition of merbau in logged-over forest in Papua, Indonesia - PRIJANTO PAMOENGKAS; ISKANDAR Z. SIREGAR; AJI NURALAM DWISUTONO (Biodiversitas Journal of Biological Diversity, 2018)
Pamoengkas P, Siregar IZ, Dwisutono AN. 2018. Stand structure and species composition of merbau in logged-over forest in Papua, Indonesia. Biodiversitas 19: 163-171. Single selective cutting is the most common form of timber extraction in natural forest in the tropics. Although, vast tracts natural forests are already logged-over, the effect of logging on the structure and species composition has been sparsely documented, especially for merbau (Intsia bijuga). Merbau is an excellent timber species and intensively harvested in Papua. The objective of this study was to analyze the structure and species composition of merbau in the several logged-over forests at different ages, i.e., 1, 5, 11, 16, 21 years old after selective logging and primary forest as the reference plot. The study was conducted in February 2016 at Sarmi District, Papua. The distributions of merbau in each plot varies but when they were compared with that in the primary forest that had reached 9.81%. Thus, the decrease of merbau trees in the plots of logged forest areas was not significant. Index of Diversity of all growth stages was high. In general, the number of merbau seedling regeneration in the study plots are above the average value standardized in Selective Cutting and Replanting System (TPTI) regulation. With regard to the condition of sapling regeneration, we concluded that selective logging might not provide enough growing space for regeneration of merbau. Providing appropriate growing space is one of the key factors to achieve adequate merbau natural regeneration.